(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
Like other Arab poets in the modern era, the Syrian poet employed the mask technique in his poetic poems, in an effort to create an objective climate in which his poem would be created far from the monophonic sound that the lyrical poem has practiced for many centuries. The mechanisms of employing the mask technique in Syrian poetry varied for artistic requirements. And moral, the researcher sought to track, monitor and clarify its manifestations, and as a result, the monitoring of three mechanisms for this employment, including the partial employment of the mask that includes part of the poetic text, Including the total employment of the mask in the poem, which resulted in the poem of the mask, while the third mechanism is the total employment of the mask in the poetic divan, and the researcher concluded that the success in employing the mask does not depend on the space in which this technique takes over his poem, except to the extent that the poet can enrich his poem Vocal pluralism, creating a dialogue between his voice and the voice of his mask, which achieves a dramatic tendency for his poem that distances it from lyricism and subjectivity.